Short Communication: Trichomes plasticity in Lallemantia royleana under different stress - MEHERI ASKARY; SEYED MEHDI TALEBI; FARIBA AMINI; BATUL SARABADANI (Nusantara Bioscience, 2016)
Abstract. Askary M, Talebi SE, Amini F, Sarabadani B. 2016. Trichomes plasticity in Lallemantia royleana under different stress. Nusantara Bioscience 8: 128-133. Lallemantia royleana is an annual herb of Lamiaceae family, which naturally grows in various parts of Iran. This medicinal plant is used in traditional medicine. Resemble to many members of this family, the aerial parts of L. royleana were covered by different kinds of trichomes. In this study, effect of different concentrations of NaCl and nanoparticles of iron oxide were examined on the trichomes morphology as well as density. The finding results showed that two main groups of trichomes, glandular and non-glandular, were presented on outer side of epidermal cells. The ANOVA test showed significant variations in trichomes number among various treatments. The main types of glandular hairs were peltate and also capitate. The mentioned forms are mainly relevant to production and also secretion of essential oil. Nanoparticles of iron oxide had positive effects on creation of palate trichomes, while increment of salt concentrations, decreased formation of them as well as short-stalked capitate.